Pomen prometa za ljubljansko mestno aglomeracijo - Černe, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
The article is analysing transport-geographical position of Ljubljana in the context of the V. and X. European transport corridor. The article describes basic elements of integral and intermodal transport system according to the infrastructure network, traffic flows and their impact on the changing role of transport-geographical factors within the economic, spatial and functional linkage of Ljubljana and Ljubljana urban region in interregional, regional and spatial development of Slovenia.
Keywords: mesta; urbana geografija; prometna geografija; prometno omrežje; prometni tokovi; Ljubljana